2014
DOI: 10.1371/journal.pone.0085026
|View full text |Cite
|
Sign up to set email alerts
|

40LoVe and Samba Are Involved in Xenopus Neural Development and Functionally Distinct from hnRNP AB

Abstract: Heterogeneous nuclear ribonucleoproteins (hnRNPs) comprise a large group of modular RNA-binding proteins classified according to their conserved domains. This modular nature, coupled with a large choice of alternative splice variants generates functional diversity. Here, we investigate the biological differences between 40LoVe, its splice variant Samba and its pseudoallele hnRNP AB in neural development. Loss of function experiments lead to defects in neural development with reduction of eye size, which stem p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…During this process, hnRNP AB may target specific transcripts by stabilizing RNA G4 quadruplexes near the transcript's RTS. Several transcripts, including MBP, β-actin, Arc, BDNF, CAMKIIα, and Protamine 2, require hnRNP AB for their localization and transport [79][80][81][82][83]. The glycine-rich domain (GYR) of the hnRNP H/F protein interacts with Transportin 1 to facilitate nucleocytoplasmic shuttling and participate in the extranuclear transport of mRNA [84].…”
Section: Localization and Transport Of Mrnasmentioning
confidence: 99%
“…During this process, hnRNP AB may target specific transcripts by stabilizing RNA G4 quadruplexes near the transcript's RTS. Several transcripts, including MBP, β-actin, Arc, BDNF, CAMKIIα, and Protamine 2, require hnRNP AB for their localization and transport [79][80][81][82][83]. The glycine-rich domain (GYR) of the hnRNP H/F protein interacts with Transportin 1 to facilitate nucleocytoplasmic shuttling and participate in the extranuclear transport of mRNA [84].…”
Section: Localization and Transport Of Mrnasmentioning
confidence: 99%
“…With this in mind, CBF-A/hnRNPab may cotranscriptionally target cis -acting elements within nascent RNA and stabilize the formation of RNA G4 quadruplexes to sort transcripts that are not translationally active and can therefore be transported to the cellular periphery. Indeed, CBF-A/hnRNPab binds to the RTS located in the 3′ UTR of several transcripts, including the Myelin Basic Protein (MBP), β-actin, Arc, BDNF, CAMKIIα, and Protamine 2 mRNAs ( Ainger et al, 1997 ; Czaplinski et al, 2005 ; Czaplinski and Mattaj, 2006 ; Raju et al, 2008 , 2011 ; Kroll et al, 2009 ; Fukuda et al, 2013 ; Andreou et al, 2014 ). RTS binding by CBF-A/hnRNPab is required for transport and localization of all of the above transcripts to the cellular periphery where they are translated and deletion studies by siRNA or gene knockout have demonstrated impaired RTS-dependent mRNA transport in oligodendrocytes, neurons, and spermatogenic cells to specific cellular locations (reviewed in Percipalle, 2014 ).…”
Section: The Involvement Of Cbf-a/hnrnpab In Rnps Assembly Transportmentioning
confidence: 99%
“…Indeed, high levels of CBF-A/hnRNPab expression can be found in neuronal cells, in the developing neural tissues and neurogenic regions of the brains ( Rushlow et al, 1999 ; Gong et al, 2003 ) In Xenopus laevis , depletion of CBF-A/hnRNPab orthologs led to a decrease in eye size due to a general increase in apoptosis, as well as a decrease in proliferative neural tissues, with cranial neurons not being properly formed, motor neurons missing and defects in migration. Depleted neurons also show a thinner and disorganized tubulin network ( Andreou et al, 2014 ). In mice, neurospheres produced from CBF-A/hnRNPab −/− knock-out mice have reduced expression in the stem cell marker Nestin and an increase in the differentiated marker dcx.…”
Section: The Involvement Of Cbf-a/hnrnpab In Rnps Assembly Transportmentioning
confidence: 99%